An artificial water body provides habitat for an endangered estuarine seahorse species. (5th October 2016) - Claassens, Louw
Abstract: Anthropogenic development, especially the transformation of natural habitats to artificial, is a growing concern within estuaries and coastal areas worldwide. Thesen Islands marina, an artificial water body, added 25 ha of new estuarine habitat to the Knysna Estuary in South Africa, home to the Knysna seahorse. This study aimed to answer: (I) Can an artificial water body provide suitable habitat for an endangered seahorse species? And if so (II) what characteristics of this new habitat are important in terms of seahorse utilization? Four major habitat types were identified within the marina canals: (I) artificial reno mattress (wire baskets filled with rocks); (II) Codium tenue beds; (III) mixed vegetation on sediment; and (IV) barren canal floor. Seahorses were found throughout the marina system with significantly higher densities within the reno mattress habitat. The artificial water body, therefore, has provided suitable habitat for Hippocampus capensis, a noteworthy finding in the current environment of coastal development and the increasing shift from natural to artificial. Highlights: Description of new aquatic habitat created within a residential marina estate in the Knysna Estuary, South Africa. Four habitat types identified within the marina system. Abundance and distribution of Hippocampus capensis within the marina established. Seahorses found throughout marina system with significantly higher densities found within artificial structures. Artificial habitat (gabions) found to provide suitable habitat for Hippocampus capensis.